2010
DOI: 10.1186/1471-2261-10-61
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a 6-year comprehensive community trial on the awareness, treatment and control rates of hypertension in Iran: experiences from the Isfahan healthy heart program

Abstract: ObjectivesWe aimed to evaluate the changes over time in the prevalence, awareness, treatment, and control rate of hypertension in intervention and reference areas of a comprehensive community trial with reference area.MethodsData from independent sample surveys before and after implementation of the program (2001 vs.2007) were used to compare differences in the intervention and references areas over time. Hypertension was defined as blood pressure ≥140/90 mmHg in non-diabetic patients and ≥130/80 mmHg in diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 23 publications
5
30
0
Order By: Relevance
“…Similarly to limited experience from community interventions in developing countries [23-26], our study showed the short-term effect on some CVDRFs especially on BP, suggesting that lifestyle intervention can be successfully implemented in similar rural settings where the burden of hypertension is high but the awareness of them is quite low.…”
Section: Discussionsupporting
confidence: 69%
“…Similarly to limited experience from community interventions in developing countries [23-26], our study showed the short-term effect on some CVDRFs especially on BP, suggesting that lifestyle intervention can be successfully implemented in similar rural settings where the burden of hypertension is high but the awareness of them is quite low.…”
Section: Discussionsupporting
confidence: 69%
“…Among patients with type 2 DM, high BP is common at the time of diagnosis of diabetes [8]. A reduction in SBP leads to significant declines in heart failure, myocardial infarction, stroke, and other atherosclerotic events [9]. Patients in the present study who visited clinics because of fear of complications were more likely to fail in controlling hypertension as well.…”
Section: Discussionmentioning
confidence: 86%
“…51 of the included studies were quantitative and two were qualitative [22],[23]. Of the 51 quantitative studies, one was a RCT [24]; 12 were cohort studies [25]–[34], two of which were retrospective [30],[34]; three were case-control studies [35][37]; 32 were cross-sectional studies; and three were ecological studies [38]–[40]. 42 of the 53 studies (79%) were carried out in countries classified by the World Bank as high-income countries, 36 of which were in the US.…”
Section: Resultsmentioning
confidence: 99%